Challenges and Opportunities for Online Learning in India - Shanthini, Jennefer K (Recent Research Reviews Journal, 2022)
Today's digital world demands more effective learning models that allow students to actively participate/enrol in their education. Digital technology is influencing the way the instruction is delivered as well as the way the information is discovered and shared. Recently, the adoption of internet and mobile learning technologies have changed the traditional perspective of education. In India, e-learning could be the viable solution to provide education in the context of 21st century. Effective mobile and e-learning applications can be developed by conducting an analysis on the use of mobile devices and applications in online education. Despite numerous initiatives to promote the use of mobile learning for education, there are some issues that must be addressed. By considering the sudden shift towards online teaching in the rise of COVID-19 pandemic in India, this study summarizes the research findings of mobile and e-learning technologies to avoid potential complications with the implementation of this technology during any future pandemic situations in India. The proposed study also assists in understanding the current state of mobile learning technology adoption in India.
Keywords: Mobile learning; E-learning applications; Mobile devices